Salvaging the endothelium in acute respiratory distress syndrome: a druggable intersection between TLR4 and NAD+ signalling. Issue 5 (6th May 2021) - Lee, Ji Young; Stevens, Reece P.; Migaud, Marie; Stevens, Troy
The acute respiratory distress syndrome (ARDS) remains an intractable problem for intensivists, even with advancements in critical care and mechanical ventilation. Mortality rates in ARDS patients are around 35–45% [1]. However, these mortality numbers represent a conservative estimate of the ARDS healthcare impact, because survivors exhibit staggering rates of morbidity and mortality in the aftermath of their intensive care unit (ICU) stay, including neurocognitive dysfunction that can prohibit the return to activities of daily living [2, 3]. Development of medical therapies that improve both the short- and long-term outcomes of these critically ill patients remain an urgent unmet need. eNAMPT neutralisation may be effective treatment in acute respiratory distress syndrome https://bit.ly/3oaES9c